Analisis Budaya Organisasi pada Kantor Desa Pataruman - naila, ⁠naila; dicky (Jurnal Ekonomi Bisnis Manajemen Prima, 2024)
This research discusses the organizational culture found in the Pataruman Village Office. The focus of the problem analyzed is how the implications of Pataruman Village Office employees on the existing organizational culture. Organizational culture is a certain pattern owned by members and employees. The pattern starts from behavior, norms, values, to assumptions related to the integration of individuals in running it. The research method used is qualitative research with an ethnographic approach. To obtain data in this study with literature and field studies which include observation, interviews, and documentation. Interviews were conducted with four interviewees and then asked to be analyzed using credibility, transfertability, and dependability tests. The results of the research that has been done show that socialization in the form of exposure and installation of banners is only done at the beginning, some employees who misstate the value of organizational culture, there are some employees who come late and do not wear uniforms according to the rules, lack of sanctions against employees who violate the rules, and organizational culture is formed by leaders during the nomination period so that employees do not take part. The advice given by the author is to start making reports on the assessment of the implementation of organizational culture every year, the need for exposure both in the form of socialization and social media, then sanctions against violators need to be done firmly.